Ziver Divan - Sandal, Kerim (My University, 2001)
Eser, İstanbul Üniversitesi Merkez kütüphanesi Türkçe Yazmalar Kitaplığı 5453 numarayla kayıtlıdır. Eserin tamamı 56 varaktır. Eserde 185 Türkçe gazel, 1 hâtime, 1 tarih, 1 tercî-bend bulunmaktadır. Bu tezi hazırlamaktaki amacımız: Birkaç şuara tezkiresi dışında adından bahsedilmeyen divân şâiri Ahmed Zîver Efendi'yi ve eserini tanıtmak, dîvanda bulunan 1120 beyti Türk Edebiyatına kazandırmaktır. Tez giriş metin ve sözlük olmak üzere üç bölümden oluşmaktadır. Giriş bölümünde Ahmed Zîver Efendi'nin kısa bir biyografisi ve eserin hazırlanmasında yararlanılan kaynaklar verilmiştir. Metin bölümünde 185 Türkçe gazel alfabetik olarak sıralanmış ve bu sıralamada orijinal divânın sıralamasına uyulmuştur. Her gazelin vezni gazelden önce belirtilmiştir.Metindeki numaraların birincisi gazel ikincisi beyit numaralarıdır. Sözlük bölümünde ise eserde geçen bütün kelimeler alfabetik olarak sıralanmış olup madde başı olarak kabul edilen kelimelerin altına o kelimeyle ilgili ara madde, birleşik kelimeler, tamlamalar verilmiştir. Madde başı veya ara maddelerin ikinci, üçüncü unsur olarak geçtiği maddelere (--) işareti ile göndermeler yapılmıştır.

The book is registeredunderfİxture number 5453 inTurkishwrittingsection ofthe Central Library of İstanbul Universtyt. it is composed of 56 leaves. 185 Turkish lyrik poems (gazel), l epilogue(hatime), l date poem (tarih şiiri / beyti) and l long poem (tercî- bend) at the beginning ofthe book. Our purpare İn preparing this thesis is to know Divan poet Ahmed Zîver Efendi, who is not mentioned except tor a few Şuara Tezkiresi and his work and to cause the Turkish literature to gain the 1120 couplets in dîvan. The thesis consist of theree sections which are the introduction, the text and the dictionary. in the introduction section, you can fınd a short bîography of Ahmed Ziver Efendi and the sources which were a used in the preparation of the book. 185 Turkish lyric poems are listed in aiphabetical order in the text secdon according to the orginal order in divan. The meter of each lyric poem i s stated before it. Of the numbers in the text, the first one İs the lyric poem number and the second one is the couplet number. In the dictionary section; ali the words used in the book are given in aiphabetical order. The wording accepted as the beginning (main) item has down below the intermediaryitem, compound words and noun phrases related to that word, The items İdentiHed as second, third factors of the main or intermediary items have been referred with marking ( à )
Keywords: Divan Edebiyatı; Edebiyat; Osmanlıca edebiyat; Türk Edebiyatı